2004
DOI: 10.1021/es049386u
|View full text |Cite
|
Sign up to set email alerts
|

Pu(V)O2+ Adsorption and Reduction by Synthetic Magnetite (Fe3O4)

Abstract: Changes in aqueous- and solid-phase Pu oxidation state were monitored over time in magnetite (Fe3O4) suspensions containing 239Pu(V)-amended 0.01 M NaCl. Oxidation state distribution was determined by leaching of Pu into an aqueous phase followed by an ultrafiltration/solvent extraction technique. The capability of the technique to measure Pu oxidation state distribution was verified using 230Th(IV), 237Np(V), and 233U(VI) as oxidation state analogues. Reduction of Pu(V) was observed at all pH values (pH 3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 35 publications
11
140
1
Order By: Relevance
“…This suggests that Pu became more strongly associated with the solids phase over time. This "aging effect" was also observed by Powell et al (2004Powell et al ( , 2005 in similar experiments with goethite, hematite, and magnetite.…”
Section: The Role Of Redox State and Desorption Kinetics For Pu On Gosupporting
confidence: 80%
See 1 more Smart Citation
“…This suggests that Pu became more strongly associated with the solids phase over time. This "aging effect" was also observed by Powell et al (2004Powell et al ( , 2005 in similar experiments with goethite, hematite, and magnetite.…”
Section: The Role Of Redox State and Desorption Kinetics For Pu On Gosupporting
confidence: 80%
“…Reduction of Pu(V) to Pu(IV) promotes sorption due to the higher affinity of Pu(IV) for mineral surfaces, relative to Pu(V). Powell et al (2004) determined an overall rate expression describing Pu(V) reduction by hematite and goethite as a function of solution pH. In continued studies, Powell et al, (2006) found that Pu(IV) was the dominant sorbed oxidation state for all synthetic minerals tested, even on oxidizing minerals such as pyrolysite (β-MnO 2 ).…”
Section: The Role Of Redox State and Desorption Kinetics For Pu On Gomentioning
confidence: 99%
“…Similar sorption studies of Pu(V) on magnetite (Fe II Fe III 2 O 4 ) [6,7] using solvent extraction also showed reduction to Pu(IV). However, previous XAS measurements involving goethite, Fe III O(OH) [8], a mineral devoid of Fe(II), showed reduction of Pu(VI) to Pu(V) at micromolar to millimolar concentrations, but no evidence of further reduction to Pu(IV).…”
Section: Mnmentioning
confidence: 57%
“…An alternate hypothesis is that light or alpha particle induced peroxide formation may result in the reduction of Pu(V) to Pu(IV). Reduction of Pu(V) to Pu(IV) on a variety of mineral surfaces has been observed (Keeney-Kennicutt and Morse, 1985;Penrose et al, 1987;Powell et al, 2006;Powell et al, 2004;Powell et al, 2005;Sanchez et al, 1985). Most notably, Pu(V) reduction to Pu(IV) was observed on surfaces expected to be either oxidizing or non-reactive such as pyrolusite (-MnO 2 ), tuff (Pu predominantly associated with ranciete/Mn(IV) phase), hematite (-Fe 2 O 3 ), goethite (-FeOOH), and silica (SiO 2 ) (Powell et al, 2006;Powell et al, 2005).…”
Section: Pu(iv) and Pu(v) Sorption To Gibbsitementioning
confidence: 96%